Assessment of Healthcare Practitioners’ Attitudes toward Patient Safety in Hospital Settings in Saudi Arabia: A Strategy to Improve Medical Education - Abdulkarim Jayiz M. Alruwaili; Saad Dawood S. Alkubaydan; Jamal Muqbil B. Alshammari; Ibrahim Homoud E. Alkhaldi; Rayan Saud S. Alsharari; Marwa Ahmed El Naggar (Journal of Nature and Science of Medicine)
Introduction: According to the World Health Organization, patient safety (PS) aims to prevent and minimize risks, errors, and harm during healthcare delivery. Physicians’ and nurses’ attitudes significantly impact hospital safety cultures and medical error rates. Aim: This study evaluates healthcare practitioners’ attitudes toward PS in hospital settings across the Kingdom of Saudi Arabia. Materials and Methods: A cross-sectional study was conducted between February 2023 and March 2024 in five regions of Saudi Arabia, targeting a sample of 1510 healthcare providers. Data were collected using a validated structured questionnaire comprising 26 statements across nine PS subscales. Responses were recorded on a 5-point Likert scale, with six statements scored in reverse. Results: The study found that 69.12% of participants were female, with nurses comprising the largest professional group (51.34%). There was a statistically significant difference in the “Disclosure responsibility” subscale between males and females (P = 0.0006), with females showing a stronger sense of responsibility to report errors. Regional variations were also observed, particularly in “Error reporting confidence” and “Working hours as error cause,” with the Northern region expressing higher concern (P = 0.043). Conclusion: The study underscores the impact of demographic factors, professional roles, and regional differences on attitudes toward PS. It calls for targeted training and tailored safety programs to improve PS culture and reduce medical errors in Saudi Arabia.